Motivasi belajar siswa dapat meningkatkan keaktifan siswa melalui pendekatan ketrampilan proses dalam pembelajaran IPA pada siswa kelas III SD Negeri 2 Sumber kecamatan Trucuk, Kabupaten Klaten - lestari, Etik (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This research is entitled Student motivation can increase student activity through a process skills approach in science learning in class III students at SD Negeri 2 Sumber, Trucuk sub- district, Klaten Regency. Research time Dates 6, 8, 10 and 13 June 2021. In this research, the objects were students at SD Negeri 2 Sumber class III, Trucuk District, Klaten Regency with a sample population of 17 students. Both partial and simultaneous analysis models are used to test hypotheses using models Inquiry learning. The aim of learning using the inquiry model is: Helping students to develop intellectual discipline and thinking skills by asking questions and getting answers based on their curiosity. This research is a type of Classroom Action Research which aims to improve student learning achievement in learning Natural Sciences. Thus, it can be concluded that the results of research carried out at SD Negeri 2 Sumber on science subjects with the application of the inquiry learning model can improve learning achievement.